Individual and contextual predictors of children's hemoglobin levels from Southern Brazilian municipalities in social vulnerability - Débora Letícia Frizzi Silva; Doroteia Aparecida Höfelmann; Cesar Augusto Taconeli; Regina Maria Ferreira Lang; Camila Dallazen; Daniela Cardoso Tietzmann; Julia Dubois Moreira; Sara Araújo da Silva; Eduardo Augusto Fernandes Nilson; Vivian Siqueira Santos Gonçalves; Sandra Patricia Crispim (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: Few studies have investigated the simultaneous effect of individual and contextual factors on the occurrences of anemia. This study aims to evaluate the variability of children's hemoglobin levels from municipalities in social vulnerability and its association with factors of individual and municipal nature. This is a cross-sectional, multi-center study, with children data (12-59 months) collected from 48 municipalities of the Southern region of Brazil, that were included in the Brazil Without Poverty Plan. Individuals' data were collected using a structured questionnaire, and secondary and ecological data of children's municipalities were collected via national surveys and institutional websites. The outcome was defined as the hemoglobin level obtained by HemoCue. A multilevel analysis was performed using Generalized Linear Models for Location Scale and Shape using R, with a 5% significance level. A total of 1,501 children were evaluated. The mean hemoglobin level was 12.8g/dL (95%CI: 12.7-12.8), with significant variability between municipalities. Lower values of hemoglobin were observed in children who lived in municipalities with a higher urbanization rate and a lower number of Community Health Agents, in relation to the reference categories. At the individual level, lower hemoglobin values were identified for children under 24 months, not enrolled at daycares, who were beneficiaries of the conditional cash transfer program and diagnosed with underweight. The results shed light on important factors at the municipal and the individual levels that were associated to the hemoglobin levels of children living in municipalities in social vulnerability.